2015
DOI: 10.1007/s10681-014-1339-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of markers linked to late leaf spot and rust resistance, and selection of superior genotypes among diverse recombinant inbred lines and backcross lines in peanut (Arachis hypogaea L.)

Abstract: Recombinant inbred lines (RILs) from four populations involving cultivated varieties, and backcross lines from three populations involving cultivated varieties and synthetic tetraploids (developed from wild diploids) were employed for validating late leaf spot (LLS) and rust resistance-linked markers and identifying superior genotypes in peanut. GM2009, GM2301, GM2079, GM1536, GM1954 and IPAHM103 markers showed significant association with rust resistance. They were successfully validated in a new RIL (TG 19 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Several studies have emphasized the application of different types of molecular markers, construction of peanut linkage maps, or tagging of important agronomic traits, such as disease resistance Gajjar et al, 2014). Recently, many DNA markers have been found to be putatively linked to rust and LLS resistance genes (Mondal et al, 2012a;Khedikar et al, 2010;Shoba et al, 2012;Sujay et al, 2012) (Table 2), a few of which have been validated and used in the breeding programme Gajjar et al, 2014;Varshney et al, 2014). Location of markers on the various linkage groups in Table 2, is derived after doing intensive meta-analysis of all the published literature, including the most comprehensive and consensus linkage maps available in peanut.…”
Section: Markers Associated With Rust and Lls Resistance Gene(s)mentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have emphasized the application of different types of molecular markers, construction of peanut linkage maps, or tagging of important agronomic traits, such as disease resistance Gajjar et al, 2014). Recently, many DNA markers have been found to be putatively linked to rust and LLS resistance genes (Mondal et al, 2012a;Khedikar et al, 2010;Shoba et al, 2012;Sujay et al, 2012) (Table 2), a few of which have been validated and used in the breeding programme Gajjar et al, 2014;Varshney et al, 2014). Location of markers on the various linkage groups in Table 2, is derived after doing intensive meta-analysis of all the published literature, including the most comprehensive and consensus linkage maps available in peanut.…”
Section: Markers Associated With Rust and Lls Resistance Gene(s)mentioning
confidence: 99%
“…The search for peanut cultivars resistant to S. rolfsii originates all the way back Table 1 List of a few genotypes, used for mapping of various resistance gene(s) (Dwivedi et al, 2003;Shoba et al, 2012;Sujay et al, 2012). to 1918(McClintock, 1918, but a high degree of resistance is yet to be found.…”
Section: Soil-borne Fungal Diseases and Associated Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports indicated that leafspot resistance is controlled by multiple genes (Green and Wynne 1986) and several QTLs for tolerance to this disease identified using SSR markers have been reported in various RIL populations (Khedikar et al 2010;Sujay et al 2012;Wang et al 2013;Sukruth et al 2015). The objective of our current study is to precisely map QTLs conferring peanut leafspot resistance using high density sequence-based SNP marker genotyping by double digest restriction-site associated DNA sequencing (ddRAD-seq) (Baird et al 2008;Peterson et al 2012).…”
Section: Introductionmentioning
confidence: 99%